A monomeric (trimethylsilyl)methyl lithium complex: synthesis, structure, decomposition and preliminary reactivity studies. Issue 28 (2nd December 2021) - Davison, Nathan; Waddell, Paul G.; Dixon, Casey; Wills, Corinne; Penfold, Thomas J.; Lu, Erli
Abstract : In this work, a rare monomeric organolithium complex was reported, stabilised by a neutral tetradentate amine ligand. Its structure and decomposition/reactivity were studied. Abstract : Monomeric organolithium (LiR) complexes could provide enhanced Li–C bond reactivity and suggest mechanisms for a plethora of LiR-mediated reactions. They are highly sought-after but remain a synthetic challenge for organometallic chemists. In this work, we report the synthesis and characterisation of a monomeric (trimethylsilyl)methyl lithium complex, namely [Li(CH2 SiMe3 )(κ 3 - N, N ′, N ′′-Me 6 Tren)] (1 ), where Me 6 Tren is a tetradentate neutral amine ligand. The structure of 1 was comprehensively examined by single-crystal X-ray diffraction, variable temperature NMR spectroscopy and electron absorption spectroscopy. Complex 1 decomposes via ligand C–H and C–N activations to produce a Li amide complex 2 . Preliminary reactivity studies of 1 reveal CO insertion and C–H activation reaction patterns.